2019
DOI: 10.1177/0885328219882638
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, characterization, and cytotoxicity of PCL/PLGA scaffolds through plasma treatment in the presence of pyrrole for possible use in urethral tissue engineering

Abstract: Electrospinning has proven to be a suitable technique for the production of small diameter tubes, with diverse applications, in the field of tissue engineering. In this work, tubular scaffolds were prepared by electrospinning a polycaprolactone/polylactic-co-glycolic acid (PLGA) blend and then treated with polypyrrole plasma for a possible application with urethral tissue. Scanning electron microscopy micrographs showed that for 10% and 20% of the PLGA in the blend, the microfibers, of varying diameters, were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…Caixia Peng et al [ 42 ] made scaffolds of PCL/PLGA in different proportions (1:90, 50:50, 90:10) reporting good degradation properties, surface characteristics, and cellular activities, demonstrating that the PCL/PLGA (50:50) possessed potential in tissue engineering. These concentrations are very similar to those described by Sanchez-Pech [ 31 ] that, demonstrated that scaffolds made by electrospinning of PCL and PLGA (70:30) were not toxic, and the pore sizes and distances between fibers allowed the migration and proliferation of urethral cells, concluding that the mixture with these percentages is recommended for urethral tissue engineering, as it facilitates the turnover of nutrients and oxygen, an important characteristics for proper tissue repair and regeneration. The evaluation of the PCL/PLGA (80:20) scaffold by SEM ( Figure 6 ) shows results that fully agree with what was previously reported by Sanchez-Pech [ 31 ] regarding the pore size and diameter of the fibers.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Caixia Peng et al [ 42 ] made scaffolds of PCL/PLGA in different proportions (1:90, 50:50, 90:10) reporting good degradation properties, surface characteristics, and cellular activities, demonstrating that the PCL/PLGA (50:50) possessed potential in tissue engineering. These concentrations are very similar to those described by Sanchez-Pech [ 31 ] that, demonstrated that scaffolds made by electrospinning of PCL and PLGA (70:30) were not toxic, and the pore sizes and distances between fibers allowed the migration and proliferation of urethral cells, concluding that the mixture with these percentages is recommended for urethral tissue engineering, as it facilitates the turnover of nutrients and oxygen, an important characteristics for proper tissue repair and regeneration. The evaluation of the PCL/PLGA (80:20) scaffold by SEM ( Figure 6 ) shows results that fully agree with what was previously reported by Sanchez-Pech [ 31 ] regarding the pore size and diameter of the fibers.…”
Section: Discussionsupporting
confidence: 87%
“…The sensitivity to the ratio of both polymers can be explained by the fact that during scaffold processing by electrospinning, the morphology of the PLGA/PCL fibers is affected by the percentage of the components. In this sense, it has been described that increasing the amount of PLGA modifies the average diameter of the fibers and their distribution; for example, Sanchez-Pech et al, in2020 reported a reduction in fiber diameter starting at added 10% 20%, and 30% of PLGA in the PCL matrix and pore size decreases when the PLGA content increases [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They concluded that the PCL/PLGA scaffolds treated with PPy plasma for 25 and 30 minutes exhibited cytotoxicity when compared with scaffolds treated for 15 minutes. 52…”
Section: Discussionmentioning
confidence: 99%
“…It is especially important for the regeneration of multilayer hierarchically organized structures, such as the urinary tract wall, as this parallel spatial architecture allows the regenerating tissue to maintain its orientation. Moreover, electrospinning allowed for the creation of small-diameter tubes with high uniaxial mechanical resistance appropriate for urethral surgery, as demonstrated by Sánchez-Pech et al (2019) The significant advantage of their work is that it includes extensive biomechanical analysis, which is usually only provided marginally. Composite tubular scaffolds created from PCL and PLGA exhibited a high elastic modulus (19 MPa), ideal to withstand bursting pressure within the human urethra.…”
Section: Biomaterialsmentioning
confidence: 99%